ANALISIS TENTANG PROFESIONALISME GURU STUDI KASUS PADA GURU-GURU BAHASA INGGRIS SERTIFIKASI PADA MADRASAH ALIYAH DI KABUPATEN LOMBOK BARAT - ., BUYUNG; ., Prof. Dr. A. A. I. Ngurah Marhaeni,MA; ., Prof. Dr. Nyoman Dantes (Jurnal Pendidikan Bahasa Inggris, 2013)
This study aims to investigate of English teachersÃ¢â¬â¢ professionalism of MA in West Lombok. The TeachersÃ¢â¬â¢ professionalism which was analyzed was on (1) the certified English teachersÃ¢â¬â¢ perception about professionalism, (2) lesson plan, (3) teaching performance. The participants in this research were twenty one certified English teachers in West Lombok. Method used in this study was qualitative. The data were collected using quantitative method which was followed by qualitative method. The data were collected through some methods of data collection: questionnaire, observation sheet, and the scoring rubric of lesson plan. The data analysis used mix method where some of the data were analyzed qualitatively and some were analyzed quantitatively. The result of the research shows that: English Teachers of MA in west Lombok met the criteria of English TeachersÃ¢â¬â¢ professionalism where pedagogy competency is categorized as good, professional competency is categorized as adequate, personality competency is categorized as good, and social competency is categorized as good. Meanwhile, the English teachersÃ¢â¬â¢ lesson plan is categorized good, the teachersÃ¢â¬â¢ performance in teaching is categorized as good, and the correlation between teacherÃ¢â¬â¢s perception and lesson plan contribute significantly on teacherÃ¢â¬â¢s performance in teaching and learning process.keyword : TeachersÃ¢â¬â¢ professionalism, pedagogy competency, professional competency, personality competency, social competency